Analysis of 3D compression via fringe projection profilometry techniques - Chan, Alvin Ming Kai (Nanyang Technological University, 2023)
Due to the increasing availability of accurate and affordable 3D data acquisition methods and tools, there is now a higher demand than ever for a high 3D compression ratio format. This project focuses on 3D compression methods inspired by fringe projection profilometry (FPP). Specifically, it investigates the viability of using alternative graphics rendering pipelines, such as modern 3D modeling software (Blender), to assist in the compression of 3D models. The creation of a virtualized FPP and direct depth encoding were used in this project. The project also evaluated the usage of alternative 2D image compression formats. Additionally, methods to overcome the loss of back-facing information were proposed.